The Influence of Drilling Process on the Neighboring Soils: A Cause Study in the East Baghdad Oil Field - Al-Mamory, Anhar; Khwedim, Kareem (Iraqi Journal of Science, 2024)
The study aims to determine the concentrations of major oxides and trace elements in the soil of East Baghdad oil field. Twenty-five soil samples were collected, 24 samples from the East Baghdad oil field and one sample was taken from Diyala governorate, far away from pollution resources (BA). The samples were analysed using X-ray fluorescence (XRF), and the result showed that SiO2 and CaO are the most abundant, followed by other oxides (Na2O, Al2O3, Fe2O3, MgO, K2O, TiO2) with a high percentage of LOI. Trace elements showed that the average values of (Cd, Co, Cr, Cu, Mn, Ni, Pb, Sr, V, Zn ) were above the international limits of the soil except for the Fe element within the international limits. High concentrations of trace elements were observed in all soil samples, exceeding the international standard limits in soil. The values of the trace elements suggest that oil industries, oil drilling and extraction operations, and human activities are the most important cause of increasing concentrations of trace elements in the soil of the study area.